2008
DOI: 10.1038/hdy.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

Vivipary as a tool to analyze late embryogenic events in maize

Abstract: In maize vivipary, the precocious germination of the seed while still attached to the ear, is the diagnostic phenotype of mutants, which are impaired in the biosynthesis or response to abscisic acid (ABA). Of the 15 genes so far described, 12 control specific steps in ABA biosynthesis, two mediate hormone response and one still has an undefined role. We have analyzed a collection of 25 independent vp isolates with the aim of determining the degree of mutational saturation that has so far been reached. Of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…For example, in Arabidopsis, seeds of the fus3-3 mutant are desiccation sensitive whereas seeds bearing the fus3-T mutation are desiccation-tolerant but exhibit reduced seed longevity in open storage [99]. In maize, the screening of 25 vp mutant seeds impaired in the synthesis of ABA to various degrees also showed a range of desiccation sensitivities [98].…”
Section: Perspectives: the Challenges Of Desiccomicsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in Arabidopsis, seeds of the fus3-3 mutant are desiccation sensitive whereas seeds bearing the fus3-T mutation are desiccation-tolerant but exhibit reduced seed longevity in open storage [99]. In maize, the screening of 25 vp mutant seeds impaired in the synthesis of ABA to various degrees also showed a range of desiccation sensitivities [98].…”
Section: Perspectives: the Challenges Of Desiccomicsmentioning
confidence: 97%
“…ABI3, LEC2 and FUS3 are B3 transcription factors interacting with each other to regulate many developmental processes such as accumulation of storage reserves and anthocyans, precocious germination, dormancy and desiccation tolerance (for references see [26,95,96]. The severe alleles must be rescued before the loss of water during maturation kills the seeds [97,98]. Recent studies reported on mutants that exhibit a range of desiccation sensitivities, thereby providing a valuable tool for the dissection of the genetic basis of desiccation tolerance by "omics" approaches.…”
Section: Perspectives: the Challenges Of Desiccomicsmentioning
confidence: 99%
“…Of the six alleles of vp10 detected in a previous screen (Durantini et al 2008), only one (vp10-108) exhibits the green shoot tip phenotype characteristic of vp10-105 in its native background. However no efforts have been made so far to assay how the genetic background affects the expression of this trait.…”
Section: Isolation and Genetic Characterization Of The Vp10-105 Mutantmentioning
confidence: 98%
“…The only translocation uncovering the mutant was T-B10L, thus allowing the assignment of the mutant to the long arm of chromosome 10. Its complementation test with all known vp mutants with green seedlings of Class 3 (Durantini et al 2008) indicates that it is allelic to vp10, a gene encoding CNX1, a multifunctional protein which catalyzes the last step of the MoCo biosynthesis (Porch et al 2006).…”
Section: Isolation and Genetic Characterization Of The Vp10-105 Mutantmentioning
confidence: 99%
See 1 more Smart Citation